Single-cell sequencing technology in colorectal cancer: a new technology to disclose the tumor heterogeneity and target precise treatment - Wen, Rongbo; Zhou, Leqi; Peng, Zhiying; Fan, Hao; Zhang, Tianshuai; Jia, Hang; Gao, Xianhua; Hao, Liqiang; Lou, Zheng; Cao, Fuao; Yu, Guanyu; Zhang, Wei (Frontiers in Immunology, 2023)
Colorectal Cancer is one of the most common gastrointestinal tumors, and its high tumor heterogeneity makes traditional sequencing methods unable to obtain information about the heterogeneity of individual cancer cells in colorectal cancer, therefore, single-cell sequencing technology can be applied to better analyze the differences in genetic and protein information between cells, so as to obtain the genomic sequence information of single cells and more thoroughly analyze the cellular characteristics and interactions in the microenvironment of colorectal cancer. This will provide a more comprehensive understanding of the development and metastasis of colorectal cancer and provide an indication of the treatment plan and prognosis. In this paper, we review the application of single-cell sequencing to analyze the TME of CRC, explore the mechanisms involved in the metastasis and progression of CRC, and improve CRC treatment options.